Pengembangan dan Pemberdayaan Potensi Desa Sabdodadi Kapanewon Bantul Kabupaten Bantul Daerah Istimewa Yogyakarta - Purnomo, Prasetyo Sidi (Jurnal Atma Inovasia, 2022)
Abstract— Through the Research and Community Service Institute (LPPM), Atma Jaya University Yogyakarta carries out the Community Service 5.0 program which focuses on community service programs through courageous means without direct contact with local residents, with a bold overall mechanism process, starting from taking, program, to implementation of the work program. The KKN 49 group was located in Sabdodadi Village, Kapanewon Bantul, Bantul Regency, Sepecial Region of Yogyakarta. Sabdodadi village has several potentials, such as cultural potential, tourism potential, and natural resource potential (SDA). Based on the potential of existing natural resources, the KKN 49 group will make village potentials regarding "Processing the Production of Banana Fruits in Sabdodadi Village into Banana Nuggets". Utilization of this potential is expected to improve the village economy through the culinary industry. The group also found data where from 2019 to 2020 there was a decrease in the number of tourist attraction visitors so that their income also decreased. In addition, there was a decline in the production value of the clothing and leather industry. So to boost the economy of the clothing and leather industry, the KKN 49 group made a pocket book on "How to Marketing Leather Crafts Online with Instagram Business and Whatsapp Business". Abstrak— Melalui lembaga penelitian dan Pengabdian masyarakat (LPPM) Universitas Atma Jaya Yogyakarta mengusung program KKN Society 5.0 yang berfokus pada program pengabdian masyarakat melalui sarana daring tanpa adanya kontak seccara langsung dengan warga sekitar, dengan proses mekanisme keseluruhan secara daring, mulai dari pengambila, penentuan program, hingga pelaksanaan pembuatan program kerja. Kelompok KKN 49 mendapatkan lokasi di Desa Sabdodadi, Kapanewon Bantul, Kabupaten Bantul, Daerah Istimewa Yogyakarta. Desa Sabdodadi memiliki beberapa potensi, seperti potensi budaya, potensi wisata, dan potensi sumber daya alam (SDA). Berdasarkan potensi sumber daya alam yang ada, kelompok KKN 49 akan membuat potensi desa tentang “Pengolahan Hasil Produksi Buah Pisang Desa Sabdodadi menjadi Nugget Pisang”. Pemanfaatan potensi ini diharapkan dapat meningkatkan perekonomian desa melalui industri kuliner. Kelompok juga menemukan data di mana pada tahun 2019 sampai tahun 2020 terjadi penurunan jumlah pengunjung objek wisata sehingga pendapatannya juga menurun. Selain itu, terjadi penurunan nilai produksi industri sandang dan kulit. Sehingga untuk mendongkrak ekonomi industri sandang dan kulit, kelompok KKN 49 membuat buku saku tentang “Cara Pemasaran Kerajinan Kulit Secara Online dengan Instagram Business dan Whatsapp Business”.